The Vasomotor Response to Dopamine Is Altered in the Rat Model of l‐dopa‐Induced Dyskinesia. Issue 4 (2nd November 2020) - Booth, Samuel; Ramadan, Abdullah; Zhang, Dali; Lu, Lingling; Kirouac, Gilbert; Jackson, Michael F.; Anderson, Chris; Ko, Ji Hyun
ABSTRACT: Background: Levodopa (l ‐dopa) is the frontline treatment for motor symptoms of Parkinson's disease. However, prolonged use of l ‐dopa results in a motor complication known as levodopa‐induced dyskinesia (LID) in 50% of patients over 5 years. Objectives: We investigated neurovascular abnormalities in a rat model of LID by examining changes in angiogenesis and dopamine‐dependent vessel diameter changes. Methods: Differences in striatal and nigral angiogenesis in a parkinsonian rat model (6‐OHDA lesion) treated with 2 doses of l ‐dopa (saline, 2, and 10 mg/kg/day subcutaneous l ‐dopa treatment for 22 days) by 5‐bromo‐2'‐deoxyuridine (BrdU)‐RECA1 co‐immunofluorescence. Difference in the vasomotor response to dopamine was examined with 2‐photon laser scanning microscopy and Dodt gradient imaging. Results: We found that the 10 mg/kg l ‐dopa dosing regimen induced LID in all animals (n = 5) and induced significant angiogenesis in the striatum and substantia nigra. In contrast, the 2 mg/kg treatment induced LID in 6 out of 12 rats and led to linearly increasing LID severity over the 22‐day treatment period, making this a promising model for studying LID progression longitudinally. However, no significantly different level of angiogenesis was observed between LID versus non‐LID animals. Dopamine‐induced vasodilatory responses were exaggerated only in rats that show LID‐like signs compared to the rest of groups. Additionally, in juvenile rats, we showed that DA‐induced vasodilation is preceded by increased Ca 2+ release in the adjacent astrocytes. Conclusion: This finding supports that astrocytic dopamine signaling controls striatal blood flow bidirectionally, and the balance is altered in LID. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.